The Use of Snowball Throwing in Teaching Reading at The Second Year Students of SMPN 8 Palopo - Wahidin, Wahidin (Faculty of Education and Teacher Training of IAIN Palopo, 2020)
This thesis uses snowball to improve student reading with the research question,